Design of power‐blocks for medium‐scale supercritical carbon dioxide plants. (20th June 2020) - Giovannelli, Ambra; Archilei, Erika M.; Di Lorenzo, Giuseppina; Salvini, Coriolano; Bashir, Muhammad A.; Messina, Giuseppe
Summary: For power production, the emerging technologies of supercritical carbon dioxide (S‐CO2 ) cycles show potential advantages if compared to conventional plants. The current bottleneck in exploiting such cycles is the development of novel components such as turbomachines and heat‐exchangers. This paper focuses on the layout arrangement and machinery design of a novel power‐block for a 10 to 15 MW supercritical carbon dioxide plant. The applied design procedure involves 0D and 1D models implemented using an in‐house Fortran code, and 3D computational fluid dynamics ( CFD) analyses using ANSYS‐CFX. Novel configurations of the power block were designed, starting with the same primary thermal source. At nominal conditions, expected overall output powers from 13.2 to 16.2 MW were found. Finally, some qualitative considerations were included in the discussion to compare the analysed arrangements.